Experimental Study on Mechanical Properties of Freeze-Thaw Damaged Red Sandstone under Combined Dynamic and Static Loading - Song-hua Mei (Hindawi Limited, 2021)
Using the freeze-thaw cycle test chamber, the red sandstone samples are subjected to cyclic freeze-thaw tests. The physical properties, static mechanical properties of freeze-thaw damage rocks, and the compressional wave velocity at specific axial pressure are measured using conventional physical tests and uniaxial compression tests. The mechanical properties of freeze-thaw damage rocks under dynamic and static loading were studied using Hopkinson pressure bar which can exert axial pressure. The studies show that, with the increase of freeze-thaw cycles, the surface layer of the rock sample undergoes spalling phenomenon, the weight gradually decreases, the sample compactness becomes worse, there are microcracks between the cemented particles, and the compressive strength and elastic modulus decrease. Under the static loading, the longitudinal wave velocity of freeze-thaw damaged samples change significantly compared with that of samples without freeze-thaw. The freeze-thaw damage degree, axial pressure, and strain rate are coupled with each other, which together affect the dynamic mechanical properties of samples, and make the variation of mechanical parameters, such as dynamic peak strength and dynamic elastic modulus of rock. The combined action of freeze-thaw damage and axial pressure weakens the strain rate effect of samples, but when the incident wave of SHPB test is same, the dynamic strength and elastic modulus of freeze-thaw damaged samples are reduced compared with those without freeze-thaw. Combining with strain equivalence principle, the constitutive relation of freeze-thaw damage of red sandstone under dynamic and static combined loading can reflect the influence of coupling damage of axial pressure and freeze-thaw, dynamic impact parameters, and other factors, which are in good agreement with the test results.